2023
DOI: 10.1108/jstpm-08-2023-0146
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the factors affecting the acceptance of blockchain in telemedicine through an integrated model approach

Fatima Shaukat,
Muhammad Shafiq,
Atif Hussain

Abstract: Purpose As a little research has been conducted to understand the factors influencing users’ intentions to adopt blockchain-based telemedicine (BBT), it is important to investigate BBT acceptance as incorporation of blockchain technology can solve telemedicine-related issues. Accordingly, this study aims to investigate the factors influencing behavioral intentions (BI) to adopt BBT. Design/methodology/approach An integrated model comprising the constructs taken from technology–organization–environment framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…Although Shaukat et al (2023) found that perceived usefulness positively influences behavioral intention to use, H9 was rejected as there was no significant correlation between them. In Dbesan et al's (2023) study, effort expectancy directly affected the behavior intention to use blockchain technology in healthcare.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although Shaukat et al (2023) found that perceived usefulness positively influences behavioral intention to use, H9 was rejected as there was no significant correlation between them. In Dbesan et al's (2023) study, effort expectancy directly affected the behavior intention to use blockchain technology in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Their study demonstrated positive correlations between perceived usefulness and attitude towards use, perceived ease of use and attitude towards use, attitude towards use and intention to use, as well as intention to use and actual usage of blockchain technology. Additionally, Shaukat et al (2023) proposed a framework that integrates four technology acceptance models, including the TAM and UTAUT. The study investigated the factors influencing the acceptance of blockchain in telemedicine.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations